2020
DOI: 10.1007/s12274-020-2858-x
|View full text |Cite
|
Sign up to set email alerts
|

The potentially crucial role of quasi-particle interferences for the growth of silicene on graphite

Abstract: A comprehensive picture of the initial stages of silicene growth on graphite is drawn. Evidence is shown that quasiparticle interferences play a crucial role in the formation of the observed silicene configurations. We propose, on one hand, that the charge modulations caused by those quantum interferences serve as templates and guide the incoming Si atoms to self-assemble to the unique (√3×√3)R30° honeycomb atomic arrangement. On the other hand, their limited extension limits the growth to about 150 Si atoms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…142 143 In order to solve the apparent contradiction with experimental results that indicate the formation of a single phase with higher strain, DFT calculations for small silicene islands have been undertaken. 144 It appears that for islands below a size of 50 atoms, the ð ffiffiffi…”
Section: Silicene On Lamellar Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…142 143 In order to solve the apparent contradiction with experimental results that indicate the formation of a single phase with higher strain, DFT calculations for small silicene islands have been undertaken. 144 It appears that for islands below a size of 50 atoms, the ð ffiffiffi…”
Section: Silicene On Lamellar Substratesmentioning
confidence: 99%
“…143 In order to solve the apparent contradiction with experimental results that indicate the formation of a single phase with higher strain, DFT calculations for small silicene islands have been undertaken. 144 It appears that for islands below a size of 50 atoms, the reconstruction is more stable than the one. Ab initio molecular dynamics (AIMD) simulations showed that the incoming flux of Si atoms could prevent the 2D islands to convert into 3D islands.…”
Section: Silicene On Other Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Several groups have experimentally synthesized silicene in recent years and characterized its basic properties. [11][12][13] Through a theoretical study, it has been found that silicene has a quantum abnormal Hall effect and photoinduced topological phase transition. 14,15 In addition, Yokoyama 16 demonstrated that a complete polarization valley and spin transport could be realized in ferromagnetic silicene.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, to overcome this limitation, various experiments have been carried out on C-based inert substrates such as highly oriented pyrolytic graphite (HOPG) with hexagonal atomic arrangements. On this substrate, the results demonstrated that the charge modulations caused by quantum interferences (QI) serve as templates and guide the incoming Si atoms to self-assemble in 2D clusters . The restricted extension of these QI limits the growth to very tiny 2D Si-ene flakes in the nanometer range and causes the transition to a 3D growth mechanism resulting in small 3D clusters at the outskirts of the tiny 2D Si-ene areas as observed experimentally. , The size limitation also originates from the presence of high defect densities on the HOPG substrate, which favor both intercalation of silicon underneath the top surface (even at room temperature), resulting in the formation of buried silicene, , and the preferential defect-assisted 3D cluster nucleation at the origin of the transition between layer-by-layer growth and Volmer–Weber growth.…”
Section: Introductionmentioning
confidence: 99%